Perceptions of Faculty of Islamic Economics and Business (FEBI) Students on Sharia Labels: An Experience in Indonesia - Sumanti, Eva; Helmina, Helmina (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
This study highlights the knowledge of students at the Faculty of Economics and Islamic Business (FEBI) regarding the lack of information about LKS products labelled as sharia-compliant, so that this knowledge can later be applied in daily life in accordance with Islamic law. This study aims to determine the opinions, views, or perceptions of students at the Faculty of Economics and Islamic Business (FEBI) at one of the State Islamic Universities regarding sharia labels on various products offered by Sharia Financial Institutions (LKS). The study uses a qualitative research method. The data sources included primary sources from interviews with several FEBI students and secondary data from reference materials such as scientific articles (journals), books, and so on related to the research topic. The data collection methods used included interviews and documentation. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. The findings of this study indicate that due to their status as academics in the field of Islamic economics and finance, students of the Faculty of Economics and Islamic Business (FEBI) have views on the sharia label on goods sold by Sharia Financial Institutions (SFIs). The use of sharia principles in the entire operating system and in the creation of SFI products is indicated by the sharia label on sharia products.